User perception on various designs of tongue scrapers: an observational survey. Issue 4 (10th February 2016) - Beekmans, DG; Slot, DE; Van der Weijden, GA
Abstract: Aim: The aim of this study was to identify the participants' preference and perception of effectiveness with respect to nine commercially available tongue scrapers. As secondary aim, perception of discomfort and suspected sharpness were assessed. In addition, the first impression of the design of the various tongue scrapers was evaluated. Materials and methods: This was an observational survey without blinding to the products. At first impression, participants were given nine tongue scrapers and were asked to immediately use all, and to point out which of the scrapers they preferred most. Subsequently, a 14‐day familiarization period followed. At the follow‐up appointment, all participants received a questionnaire which used a visual analogue scale (VAS) to evaluate their perception of the various scrapers used. Questions regarding the perceived efficacy, discomfort and pain were posed. Data were analysed statistically byanova . T ‐tests were used for ' post hoc ' analysis and Bonferroni corrections were used for multiple comparisons. Results: In total, 50 participants completed the assessment. The primary parameter 'efficacy' showed scores that ranged from 4.09 to 6.43 ( P < 0.001) for the nine tongue scrapers. The secondary parameters 'sharpness' (range from 3.31 to 6.26) and 'discomfort' (range from 5.67 to 8.33) showed significant differences as well ( P < 0.001). A significant negative correlation ( R = −0.850; P = 0.004) between the perceived sharpness and discomfort was observed. Conclusion: The perception of effectiveness varied among the various tongue‐cleaning device designs. No single feature stood out as being specifically related to perception of effectiveness. Sharpness and comfort were negatively correlated. Comfort and effectiveness were positively correlated. The results from this study indicated that participants found TS6 and TS8 to be the most comfortable and the most effective. However, TS8 scored higher for inducing a higher gag reflex.